Administrative Transaction Data - Julia Lane (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
The value of administrative transaction data, such as financial transactions, credit card purchases, telephone calls, and retail store scanning data, to study social behaviour has long been recognised. Now new types of transactions data made possible by advances in cyber-technology have the potential to further exland social scientists' research frontier. This chapter discusses the potential for such data to be included in the scientific infrastructure. It discusses new approaches to data dissemination, as well as the privacy and confidentiality issues raised by such data collection. It also discusses the characteristics of an optimal infrastructure to support the scientific analysis of transactions data.
Keywords: 330; transactions data; administrative data; cybertechnology; privacy and confidentiality; virtual organizations